PENGARUH METODE PEMBELAJARAN INDEX CARD MATCH TERHADAP HASIL BELAJAR MENENTUKAN FAKTA DAN OPINI PADA SISWA KELAS V SDN 095139 SEMANGAT BARIS - Junita Rusli Nainggolan; Mery Chris Isabella Saragih (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
Elementary school teachers play the most important role in creating quality human resources capable of competing in an era of rapid technological advancement. However, many educators, especially at SD Negeri 095139 Semangat Baris, are still found teaching material using conventional media. As a result, students feel bored and unmotivated to participate in learning activities. This study aims to determine the effect of the Index Card Match learning method on learning outcomes in identifying facts and opinions among fifth-grade students at SD Negeri 095139 Semangat Baris.This research was conducted at SD Negeri 095139 Semangat Baris with a research sample of 28 fifth-grade students. This research is quantitative in nature and uses an experimental method. The data in this study were tested for analysis requirements using the Liliefors test for normality and the F-test for homogeneity. The hypothesis was then tested using the t-test.Based on the results of the study, it was found that the average learning outcome in identifying facts and opinions for fifth-grade students in the pre-test stage was 70.92. The average learning outcome in identifying facts and opinions in the post-test stage was 77.59. With a calculated t-value of 2.544, which is greater than the t-table value of 1.674, the researcher concludes that there is an effect of the Index Card Match learning method on the learning outcomes in identifying facts and opinions among fifth-grade students at SD Negeri 095139 Semangat Baris.